DEVELOPING FLIPBOOK-BASED DIGITAL MODULE OF AKIDAH AKHLAK SUBJECT TO INCREASE STUDENTS’ LEARNING MOTIVATION - Risa Fatma Febriyanti; Zumrotul Fauziah; Pramesti Wulandari (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
Today's education requires teachers to provide learning that can utilize technology appropriately because, in this era of globalization, technology has become very important and cannot be separated from daily human life. So, teachers need to apply appropriate technology to assist the process of learning and improve learning efficacy, including using electronic devices. The Flipbook-based digital learning module is an achievement system that has been selected in light of developing a more efficient and effective education system. On that basis, the central theme of using a teaching system with Flipbook-based modules is to increase student learning motivation so that students become motivated and enthusiastic and can actively participate in learning. This research uses the R&D (Research & Development) research method. Analysis, design, development, implementation, and evaluation are the five phases that make up the ADDIE development model. The research results show that the Flipbook-based digital learning module is very suitable for use, with media expert assessment results of 92.5 percent and material experts 100 percent. Additionally, the findings of the student's learning motivation questionnaire indicate a relationship between digital learning modules and students' motivation to study.